Mongolia Economic Update, November 2015 - World Bank Group (World Bank, Washington, DC, 2015)
Mongolia’s growth sharply slowed to 3.0 percent in the first half of 2015. External demand is weakening due to a continued dampening of the commodity market and slower growth in China, translating into a drop in exports. Slowing domestic demand is largely caused by a plunge in investment due to falling foreign direct investment (FDI). Measures were taken to curb the budget deficit, debt, and off-budget expenditures. New deficit and debt ceilings were set for 2015-18 by amending the fiscal stability law (FSL) in January. The 2015 budget was amended in January to curb the structural deficit within 5 percent of gross domestic product (GDP). Growth is expected to slow in 2015-16, but a recovery in foreign investment will begin to support the growth of the non-mining sector in 2016. The Development Bank of Mongolia (DBM) is expected to provide about Mongolian Tughrik rates (MNT) 600 billion to its commercial portfolio in 2015, and to further reduce its commercial spending to MNT 300-400 billion in the next couple of years due to tight financing conditions. Under these assumptions, the commercial projects financed by the DBM are expected to around 3 percent of GDP in 2015, and decline to 1-1.5 percent of GDP in 2016.